Understanding Mineral Dust Through a Doctoral Alliance - Marenco, Franco; Amiridis, Vassilis; Costa, Maria João; Kandler, Konrad; Kazadzis, Stelios; Klose, Martina; Pérez García-Pando, Carlos; Ryder, Claire; M.Antunes, Celia; Basart, Sara; Bortoli, Daniele; Bouris, Demetri; et al. (My University, 2025)
We present an example of how a doctoral network can bring together multidisciplinary expertise and novel scientific advances in atmospheric dust. This network (Dust-DN) has started operations and is a strategic alliance of high-profile partners, able to leverage unique facilities for atmospheric research and innovative space missions. The network aims to improve our understandings of dust processes and microphysics, identify the signature of source regions, address the socio-economic impacts of dust transport and improve the quantification of the role of dust in the climate system. The first results have already been achieved and are shown here, and many more are expected to follow.
Keywords: dust; microphysics; source regions; climate; socio-economic impacts; environmental health; Earth observations; airborne research; remote sensing